EXPERIMENTAL INVESTIGATION ON THE CARBON ISOTOPE FRACTIONATION OF METHANE DURING GAS MIGRATION BY DIFFUSION THROUGH SEDIMENTARY ROCKS AT ELEVATED TEMPERATURE AND PRESSURE - Zhang T.; Krooss B.M. (My University, 2001)
Molecular transport (diffusion) of methane in water-saturated sedimentary rocks results in carbon isotope fractionation. In order to quantify the diffusive isotope fractionation effect and its dependence on total organic carbon (TOC) content, experimental measurements have been performed on three natural shale samples with TOC values ranging from 0.3 to 5.74%. The experiments were conducted at 90°C and fluid pressures of 9 MPa (90 bar). Based on the instantaneous and cumulative composition of the diffused methane, effective diffusion coefficients of the ¹²CH4 and ¹³CH4 species, respectively, have been calculated.